2011
DOI: 10.3844/ajassp.2011.1328.1336
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations of Phytoplankton Community in the Coastal Waters of Caspian Sea in 2006

Abstract: Problem statement:The Caspian Sea ecosystem has been suffered with many problems since 1980s. Aanthropogenic pollution from heavy metals, hydrocarbons, pesticides, changes in the quantity of nutrient inputs by rivers, are significant threats to biodiversity and biological resources such as plankton structure in the Caspian Sea. According to the significant of phytoplankton community in marine system. The state of the fluctuations of phytoplankton communities of the southwestern Caspian Sea was investigated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
4
9
0
Order By: Relevance
“…The findings on both nutrients and their ratios, and qualitative and quantitative phytoplankton distributions indicated that the system was underneath eutrophication processes, as were indicated in previous studies (Bagheri et al, 2010(Bagheri et al, , 2011(Bagheri et al, , 2012b. However, according to previous trophic index (TRIX) values in the study area showed that the system was mesotrophic (Nasrollahzadeh et al, 2008b).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The findings on both nutrients and their ratios, and qualitative and quantitative phytoplankton distributions indicated that the system was underneath eutrophication processes, as were indicated in previous studies (Bagheri et al, 2010(Bagheri et al, , 2011(Bagheri et al, , 2012b. However, according to previous trophic index (TRIX) values in the study area showed that the system was mesotrophic (Nasrollahzadeh et al, 2008b).…”
Section: Discussionsupporting
confidence: 60%
“…Recently, Khodaparast (2006), Bagheri et al (2011) and Nasrollahzadeh et al (2011) reported that the cyanophyte Nodularia spumigena Mertens ex Bornet and Flahault 1886 and dinoflagellate Heterocapsa sp. formed two abnormal phytoplankton blooms in the Iranian coasts of the Caspian Sea.…”
Section: Introductionmentioning
confidence: 99%
“…This correlation was significant at the 0.01 level. Nasrollahzade et al Bagheri et al (2010aBagheri et al ( , 2011a, according to both our data and previous data we suggest that the increase of phytoplankton was influenced by the discharge of the rivers which decreased the transparency in the soutwestern Caspian Sea.…”
Section: Quantitative Phytoplankton Compositionsupporting
confidence: 64%
“…Although various phytoplankton studies have been performed in the southern Caspian Sea in recent years (Hosseini et al 1998, Laloei 2001, Bagheri et al 2002, 2010a, 2011a, 2012, Ganjian and Makhlough 2003, Khodaparast 2006, Nasrollahzadeh et al 2008, there are a few phytoplankton studies in detail reported from the southwestern Caspian Sea. This study describes the temporal and spatial distributions of phytoplankton abundance and species composition in detail in the southwestern Caspian Sea in 2008 and the results were compared to studies from previous years.…”
Section: Introductionmentioning
confidence: 95%
“…e Caspian Sea has undergone signi�cant ecological alteration during the past 30 years. is could be linked to dramatic changes in the southern Caspian Sea due to increased pollution: sewage, industry effluent, and agricultural waste water discharges into the river as well as deforestation of the river's watersheds [5,6].…”
Section: Introductionmentioning
confidence: 99%